2022
DOI: 10.1002/brb3.2805
|View full text |Cite
|
Sign up to set email alerts
|

Exercise postconditioning reduces ischemic injury via suppression of cerebral gluconeogenesis in rats

Abstract: Pre‐stroke exercise conditioning reduces neurovascular injury and improves functional outcomes after stroke. The goal of this study was to explore if post‐stroke exercise conditioning (PostE) reduced brain injury and whether it was associated with the regulation of gluconeogenesis. Adult rats received 2 h of middle cerebral artery (MCA) occlusion, followed by 24 h of reperfusion. Treadmill activity was then initiated 24 h after reperfusion for PostE. The severity of the brain damage was determined by infarct v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…In our current study, we analyzed provides new evidence that CEDT is an effective rehabilitation intervention strategy for cognitive impairment after CCI. In addition to this, there are studies that have found sex differences in certain behaviors of rats with cognitive impairment, and such differences may be revealed in the specific response or degree of response to various training protocols (Li et al, 2022;Li, Geng, et al, 2023). Some studies have suggested that the reason for the sex difference may be that estrogen regulates neurotransmitter interactions (Ancelin & Ritchie, 2005), affects metabolism and antioxidants, reduces ischemic damage (Brinton, 2008), and lowers inflammatory responses (Straub, 2007), among others.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, we analyzed provides new evidence that CEDT is an effective rehabilitation intervention strategy for cognitive impairment after CCI. In addition to this, there are studies that have found sex differences in certain behaviors of rats with cognitive impairment, and such differences may be revealed in the specific response or degree of response to various training protocols (Li et al, 2022;Li, Geng, et al, 2023). Some studies have suggested that the reason for the sex difference may be that estrogen regulates neurotransmitter interactions (Ancelin & Ritchie, 2005), affects metabolism and antioxidants, reduces ischemic damage (Brinton, 2008), and lowers inflammatory responses (Straub, 2007), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it upregulated pro-apoptotic proteins (e.g., Caspase-3), inducing cell apoptosis, while downregulating neurovascular remodeling proteins [e.g., synaptophysin (SYP)][ 11 12 13 14 ]; moreover, very early exercise inhibited hypoxia inducible factor-1α (HIF-1α) degradation and promoted incomplete gluconeogenesis, resulting in exacerbated lactic acidosis and oxidative stress injury. [ 15 16 ] It also amplified endoplasmic reticulum stress and activated the CCAAT-enhancer binding protein (C/EBP)-homologous protein (CHOP) and Caspase-12 mediated apoptosis pathway, further aggravating brain injury. [ 17 ]…”
Section: Optimal Timing and Intensity For Poststroke Rehabilitationmentioning
confidence: 99%